Standardization of propagation through patch budding in lasoda (Cordia myxa L.) under semi arid conditions of Rajasthan (Indian Journal of Arid Horticulture, 2018)
nd Lasoda or lehsua ( Cordia myxa L) belongs to family sowing of seeds was completed in 2 week of June, 2012 in  Boraginaceae, found growing all over the country especially plastic bags filled with a mixture of soil, FYM and sand (1:1:1)  in arid and semi arid situations so far. Lasoda is not explored and 200 g of single super phosphate per cubic meter of potting  to full potential economically and hence immediate attention mixture. One year old generative root stocks of Lasoda were  to explor the potential of its cultivation. It is a medium sized used for budding. Consisting six treatments, 20 plants per  broad leaved deciduous tree. It has great capacity to tolerate treatment and four replications, thus having 480 plants as  drought and hence quite widespread in arid and semi arid experimental material were taken for the study. Seedlings  regions of North India. Being a multipurpose tree species, it were maintained in sand conditions by providing ample  has long been associated with health, nutrition and other quantity of fertilizers, water and other requirements when  diversified uses. The Immature fruits are used as vegetable, required.. There were six treatments of budding dates
Keywords: family; growing; cubic meter